Impact of government expenditure on economic growth in different states in South Africa - Eugene Msizi Buthelezi (Cogent Economics & Finance, 2023)
This paper investigates the impact of long-run government expenditure and economic growth in different states in South Africa. Economic growth has been below the policy target of 5% stipulated in the National Development Plan Vision 2030, while government expenditure growth has been volatile but increasing at a decreasing rate. The paper uses the Vector-error correction (VEC) and Markov-switching dynamic regression with the data from 1994 to 2021. The significance of the paper is that it assesses the short and long-run impacts of government expenditure on different states of economic growth in South Africa. It is found that more government expenditure in South Africa hasn't resulted in the nation's economy growing, which is at odds with the Keynesian viewpoint. In both lower economic states, government expenditure reduces economic growth by 0.009% and 0.30%. The economy is expected to stay for 1 year in state 1, while it is expected to stay for 13 years in state 2. Government expenditure shocks were found to be detrimental to economic growth. It is recommended that fiscal authorities increase government expenditure in the short run rather than in the long run and monitor government expenditure.
Keywords: E62; H21; H5; O4; 330; economic growth; government expenditure; vector-error correction (VEC) and Markov-switching dynamic regression